The Influence of Command Style on Shooting Ability in Football Games at SMPN 2 Medan - Siregar, Epi Supriyani; Sari, Ika Purnama; Susilawati, Evi; Priono, Joko; Setiawan, Ari (FKIP - Universitas Riau, 2025)
Command style is a training method that involves direct instruction from the coach to the player with a focus on specific technique control and correction. Meanwhile, shooting in soccer refers to the player's ability to shoot towards the goal with the aim of scoring a goal. This study aims to analyze the effect of command style on shooting ability in soccer games in students at SMPN 2 Medan. This study used an experimental method with a pretest-posttest group design. The sample used was grade VIII students consisting of two groups, namely the experimental group who were given treatment in the form of training using the command style, and the control group who did not receive the treatment. Data were collected through shooting skills tests before and after treatment. The results of the data analysis showed that there was a significant increase in shooting ability in the experimental group using the command style compared to the control group. These findings indicate that the application of the command style in soccer training can improve students' shooting skills. This study makes an important contribution to developing more effective training methods to improve soccer technique skills, especially in the shooting aspect, in junior high school students.